2006
DOI: 10.1177/154405910608500913
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization Stress Induces BDNF in Rat Submandibular Glands

Abstract: Brain-derived neurotrophic factor (BDNF) promotes survival and differentiation of the cells of the central and peripheral nervous systems. BDNF has been identified in non-neural tissue, including the heart, lung, platelets, lymphocytes, and lacrimal glands. Immobilization stress modifies BDNF mRNA expression in some organs. The present study examines the effect of immobilization stress on BDNF, and its receptor TrkB, in male rat submandibular glands. Increased BDNF mRNA and protein expression were observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 24 publications
(37 reference statements)
3
53
0
Order By: Relevance
“…Tsukinoki et al (2006) found that the expression of BDNF in the rat submandibular gland is modulated by conditions of acute stress or non-stress. It has been reported that the NGF level is also altered by acute stress in this gland (Aloe et al 1986).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Tsukinoki et al (2006) found that the expression of BDNF in the rat submandibular gland is modulated by conditions of acute stress or non-stress. It has been reported that the NGF level is also altered by acute stress in this gland (Aloe et al 1986).…”
Section: Discussionmentioning
confidence: 98%
“…Oligonucleotide primers designed to amplify rat BDNF were specific for the coding region of exon 5. BDNF-specific primers were 5 0 -CAGGGGCATAGACAAAAG-3 0 (forward) and 5 0 -CTTCCCCTTTTAATGGTC-3 0 (reverse; BDNF PCR product: 167 bp; Tsukinoki et al 2006Tsukinoki et al ,2007Lee et al 2008) as designed and synthesized by Nippon Gene Laboratory. Real-time PCR for amplification of the rat b-actin housekeeping gene was performed using a LightCycler Primer/Probe set, 5 0 -CCTGTATGCCTCTGGTCGTA-3 0 (forward) and 5 0 -CCATCTCTTGCTCGAAGTCT-3 0 (reverse; b-actin PCR product: 260 bp), following the manufacturer's instructions (Nihon Gene Research Labs Inc., Sendai, Japan).…”
Section: Real-time Pcr Analysismentioning
confidence: 99%
“…Rat salivary glands have been shown to increase their expression of BDNF under acute stress conditions 22. Furthermore, BDNF plasma levels are increased by acute immobilization stress with the submandibular glands contributing to this 23.…”
Section: Introductionmentioning
confidence: 99%
“…Irie et al, 2011 reported a significant increase in BDNF expression levels in rat SMG after exposure to occlusal disharmonyinduced chronic stress for 8 weeks. Not only the chronic stress, but also the acute stress resulted in an increase in the salivary glands expression of BDNF (Tsukinoki et al 2006 andSaruta et al, 2014). It seems that changes in BDNF levels induced by stress are tissue specific, as reported by Saruta et al (2010).…”
Section: The Parotid Glandmentioning
confidence: 70%